2005
DOI: 10.1542/peds.2005-0469
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Harm Caused by Diagnostic Errors in Fibrodysplasia Ossificans Progressiva

Abstract: ABSTRACT. Background. Little is known about diagnostic errors for a disease worldwide. Such errors could alter the disease's natural history, especially if unwarranted interventions cause irreversible harm. Fibrodysplasia ossificans progressiva (FOP), a rare, autosomal dominant genetic disease characterized by episodes of permanent heterotopic ossification of soft tissues, occurs worldwide without racial, ethnic, or geographic predilection. There is no effective treatment, and soft-tissue trauma (eg, biopsies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
212
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(236 citation statements)
references
References 38 publications
7
212
0
8
Order By: Relevance
“…At the time of birth no specific disability or skeletal deformity is apparent, except for a malformed big toe; however, once heterotopic ossification begins in the first decade of life, it progresses with aggravation, leading to ankylosis of the major joints or fusion of the rib cage with subsequent severe disability and fatal respiratory failure (1)(2)(3)(4). Moreover, surgical attempts to remove heterotopic bone or incisional biopsies commonly lead to episodes of explosive and painful new bone growth (5)(6). Thus, the difficulties in obtaining human tissues for study have limited the molecular and biochemical understanding of the disease.…”
Section: Fibrodysplasia Ossificans Progressiva (Fop)mentioning
confidence: 99%
“…At the time of birth no specific disability or skeletal deformity is apparent, except for a malformed big toe; however, once heterotopic ossification begins in the first decade of life, it progresses with aggravation, leading to ankylosis of the major joints or fusion of the rib cage with subsequent severe disability and fatal respiratory failure (1)(2)(3)(4). Moreover, surgical attempts to remove heterotopic bone or incisional biopsies commonly lead to episodes of explosive and painful new bone growth (5)(6). Thus, the difficulties in obtaining human tissues for study have limited the molecular and biochemical understanding of the disease.…”
Section: Fibrodysplasia Ossificans Progressiva (Fop)mentioning
confidence: 99%
“…It is important to take into account and inform the patients suffering from this disease that minor trauma such as intramuscular immunizations, mandibular blocks, muscular trauma, falls, or colds could trigger a new episode of inflammatory swellings that will result in the ossification of these soft tissues (disease flare-up) (4,14) . Surgical attempts to obtain samples using biopsy or to remove a heterotopic bone could lead to episodes of explosive bone growth, which could be even much more severe that those caused by disease flareups (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical attempts to obtain samples using biopsy or to remove a heterotopic bone could lead to episodes of explosive bone growth, which could be even much more severe that those caused by disease flareups (14) . Therefore, it is necessary to control the environment of affected people, preventing, whenever possible, their exposure to situations that could exacerbate the disease, as well as avoiding invasive procedures in case of suspected FOP, which constitutes actions of primary care that can be performed in the primary health care level.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dental treatments are contraindicated, since they frequently bring about ossifications in the region. Recent data revealed that 67% of patients with FOP were submitted to invasive procedures and 68% received unnecessary treatments (5) , as in the case of the patient in question. Hallux shortening was not PROGRESSIVE OSSIFYING FIBRODYSPLASIA: CASE REPORT observed in some of the evaluations performed, while in others it was observed, but was not related to FOP.…”
Section: Discussionmentioning
confidence: 99%